Multimodal Imaging in Torpedo Maculopathy - Ferzana Mohammed; Bindu Susheela (Delhi Journal of Ophthalmology)
This is a case of torpedo maculopathy in a 45-year-old female which was previously diagnosed as a toxoplasma scar. The characteristic appearance on fundus examination along with the multimodal imaging characteristics helped diagnose torpedo maculopathy. A detailed comparison of various differential diagnosis of torpedo maculopathy is included.